1973
DOI: 10.1136/jnnp.36.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic muscle involvement in myasthenia gravis: A clinical and histopathological study

Abstract: SUMMARY An investigation was made into the occurrence of muscular atrophy and muscular pathology in a series of 170 patients with myasthenia gravis. The results can be summarized as follows: (1) Of the 148 patients with generalized myasthenia gravis, 14 showed local muscular atrophies. Of 10 biopsies from atrophic muscles, eight showed neurogenic changes, with or without lymphocytic infiltrations. One biopsy showed lymphocytic infiltrations only, and one showed type IL-fibre atrophy ( diameter in the female pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 23 publications
0
44
0
Order By: Relevance
“…The former is thought to exert a trophic effect in the muscle fibre (Oosterhuis and Bethlem 1973). Experiments have shown that the contents of a single vesicle (quantum) produce a small subthreshold depolarisation of the post synaptic membrane (about 1 mV) called a miniature end-plate potential.…”
Section: Pathophy Siologymentioning
confidence: 99%
See 1 more Smart Citation
“…The former is thought to exert a trophic effect in the muscle fibre (Oosterhuis and Bethlem 1973). Experiments have shown that the contents of a single vesicle (quantum) produce a small subthreshold depolarisation of the post synaptic membrane (about 1 mV) called a miniature end-plate potential.…”
Section: Pathophy Siologymentioning
confidence: 99%
“…Spontaneous activity suggestive of denervation may be found on electromyographic evaluation (C. L. Chrisman, personal communication), Similar findings occur in humans and although neurogenic atrophy has been demonstrated by muscle biopsy in about 30 per cent of human myasthenia gravis patients, there is no obvious neuropathy or myopathy. Functional denervation because of the absence of trophic effects of acetylcholine on muscle membrane is suspected (Oosterhuis and Bethlem 1973).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…2-C (1,2). In such cases, muscular atrophy usually involves the tongue, the scapulohumeral muscles, or the proximal limb muscles; facial muscular atrophy is relatively rare (2,3,9,10 (3,4).…”
Section: F I G U R E 2 Ne E D L E E L E C T R O My O G R a P H Y O mentioning
confidence: 99%
“…In these cases, the facial muscles were relatively rarely involved (2)(3)(4). Since then, the number of papers dealing with muscle atrophy in MG patients has decreased significantly.…”
Section: Introductionmentioning
confidence: 99%
“…While the primary site of pathology in MG is the neuromuscular junction, muscle changes also occur. Lymphocyte infiltrates and muscle fiber atrophy are the most commonly described changes in the muscle of patients with MG [1]- [4]. While modern diagnostic techniques have made muscle biopsy obsolete in the diagnosis of MG, an understanding of the spectrum of muscle pathology in MG can still be pertinent to clinical practice.…”
Section: Introductionmentioning
confidence: 99%